Microplastic contamination in filter-feeding bivalves inhabiting the natural ecosystem of Da Nang Bay: An investigation of oysters (Ostrea rivularis) and green mussels (Perna viridis) - Nguyen, Thi Hue; Nguyen , Thi Huong Thuy; Tran, Thu Thuy; Trinh , Thi Minh Trang; Pham , Thi Dung; Duong, Thi Lim; Nguyen, Viet Cuong; Nguyen, Thi Lan Huong; Nguyen , Quang Bac; Duong, Cong Dien; et al. (Vietnam Journal of Marine Science and Technology, 2025)
Microplastic (MP) contamination in marine organisms has been observed globally, especially in bivalve species inhabiting estuarine and coastal environments. In this study, microplastics are present in bivalve animals (i.e., oysters (Ostrea rivularis) and green mussels (Perna viridis)) that grow and develop in the natural environment in the Da Nang Bay area. These seafood species are produced abundantly in the region and are preferred by both visitors and residents for their daily consumption. MPs are fully characterized through abundance, shape, size, and color. MPs were detected in 100% of the examined bivalves, with an average density of 3.5 ± 2.8 items/g tissue, above the average levels seen in seafood throughout Asia. The concentration of MPs in bivalve species in the region varies from 3 items/individual to 47 items/individual, with oysters averaging 11.0 ± 5.0 items/individual and mussels averaging 18.0 ± 8.8 items/individual. Mussels have a considerably higher accumulation of MPs compared to oysters. The major component of MPs found in filter-feeding bivalve organisms consists of black plastic particles smaller than 0.5 mm in size and in fibrous form. There is a notable difference in the size of MPs between oysters and mussels, with a greater prevalence of larger MPs in oysters compared to mussels. This is a caution for MP contamination in creatures inhabiting the Da Nang Bay region. Consequently, it is essential to promptly implement steps to mitigate microplastic contamination in the research region.